StreamSculptor: Hamiltonian Perturbation Theory for Stellar Streams in Flexible Potentials with Differentiable Simulations - Jacob Nibauer; Ana Bonaca; David N. Spergel; Adrian M. Price-Whelan; Jenny E. Greene; Nathaniel Starkman; Kathryn V. Johnston (The Astrophysical Journal)
Stellar streams are one of the most promising tracers of low-mass dark-matter subhalos. Existing frameworks for modeling stream perturbations rely on restrictive assumptions for the Milky Way potential (e.g., static, axisymmetric) or are computationally inefficient in generating many realizations of subhalo impacts. We present StreamSculptor , a GPU accelerated code that combines differentiable simulations and Hamiltonian perturbation theory to model the leading-order effect of dark-matter subhalos on stellar streams. Our model works in two stages: First, a base stream is generated in a Milky Way potential, including the effects of nonlinear time-dependent sources like the rotating Galactic bar and a massive satellite galaxy. Then, linear perturbation theory is applied to the base stream, allowing us to rapidly superimpose the effects of different subhalo impacts without having to carry out additional simulations. Subhalo masses and scale-radii can be rescaled as a postprocessing step. We demonstrate how this framework can be used to model subhalo impacts on stellar streams under realistic Milky Way conditions, specifically for an inner Galaxy stream like Palomar 5 and an outer Galaxy stream like Orphan–Chenab. We find that simultaneously modeling subhalo impacts and other time-dependent components of the Galactic gravitational potential is crucial for an unbiased inference of dark-matter substructure.